2016
DOI: 10.2147/ijn.s105543
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of magnetic Fe<sub>3</sub>O<sub>4</sub> nanoparticles coloaded with homoharringtonine on human leukemia cells in vivo and in vitro

Abstract: Homoharringtonine (HHT), a natural cephalotaxine alkaloid, has been used in the People’s Republic of China for treatment of leukemia for >3 decades. Here, we employed magnetic Fe 3 O 4 nanoparticles (MNP-Fe 3 O 4 ) to improve the therapeutic effect of HHT and investigated its biological effects. Within a certain range of concentrations, the HHT-MNP-Fe 3 O 4 showed a more enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Moreover, the scientific community in Western countries has also identified the underlying plants linked to these natural products, especially the latent natural products of medicinal plants used in traditional Chinese medicine (TCM) [18]. Homoharringtonine (HHT) was first extracted from Cephalotaxus harringtonia (Knight ex J. Forbes) K. Koch and Cephalotaxus fortunei Hook [19] and has been used clinically to treat leukemia [20]. In recent years, HHT has also been used in research on various solid tumors, such as bladder, kidney, lung, and colorectal cancer [21][22][23][24].…”
mentioning
confidence: 99%
“…Moreover, the scientific community in Western countries has also identified the underlying plants linked to these natural products, especially the latent natural products of medicinal plants used in traditional Chinese medicine (TCM) [18]. Homoharringtonine (HHT) was first extracted from Cephalotaxus harringtonia (Knight ex J. Forbes) K. Koch and Cephalotaxus fortunei Hook [19] and has been used clinically to treat leukemia [20]. In recent years, HHT has also been used in research on various solid tumors, such as bladder, kidney, lung, and colorectal cancer [21][22][23][24].…”
mentioning
confidence: 99%
“…Firstly, magnetic Fe 3 O 4 nanoparticles were first prepared by reference. 24 10 mg Fe 3 O 4 dispersed in 5 mL chloroform and 20 mg dopamine dissolved in 3 mL dimethyl sulfoxide were added into a flash bottle successively. The reaction mixture was vigorously stirred to form a homogeneous solution and was heated at 70°C for 2 h before being cooled down to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…They found cell death was caused due to apoptosis and observed cell cycle arrest at G0/G1 phase. Moreover, in vivo studies explained the combination worked efficiently to decrease the tumor volume compared to drug alone (Chen et al 2016 ). A similar study explained the combination of Fe 3 O 4 with adriamycin or daunorubicin drugs showed a potential inhibitory effect on lymphoma.…”
Section: Iron Oxide Nanoparticles As Delivery Agentsmentioning
confidence: 99%
“…Results showed this drug loaded NPs can be efficiently delivered into blood brain barrier and can act as promising drug to treat blood tumors Xuhua Mao ( 2016 ) Homoharringtonine conjugated Fe 3 O 4 NPs 11.2 Used for in vitro and in vivo chemotherapy towards hematological malignancy. Results indicated drug conjugated MNPs injected in tumor bearing mice (leukemia) showed a significant decrease in tumor growth compared to drug treatment alone Chen et al ( 2016 ) Liposome with paclitaxel and SPIONs 159–168 Comprising both MRI and antitumor characteristics. Results showed the tumor growth was supressed in MDA-MB-231 tumor-bearing mice compared to controls Zheng et al ( 2018 ) Fe 3 O 4 NPs with adriamycin and daunorubicin Used as a combination therapy to treat lymphoma.…”
Section: Iron Oxide Nanoparticles As Delivery Agentsmentioning
confidence: 99%